A Qualitative Exploration of Community Integration in SME Management Strategies - Rumasukun, Mohammad Ridwan; Noch, Muhammad Yamin; Putra, Aditya Halim Perdana Kusuma (Manunggal Halim Jaya, 2024)
This qualitative study aims to explore community integration within Small and Medium Enterprises (SMEs) and its implications for organizational success and societal well-being. The research methodology involved a systematic literature review, employing thematic analysis and constant comparison to synthesize existing literature on the topic. Key themes emerged regarding strategies employed by SMEs to foster community integration, including Corporate Social Responsibility (CSR) initiatives, stakeholder engagement, and collaboration with local institutions. The findings underscore the pivotal role of CSR practices in building trust and fostering long-term relationships with stakeholders. Additionally, stakeholder engagement strategies were identified as essential for involving community members in decision-making processes and co-creating solutions that address local needs. Collaboration with local institutions emerged as critical for promoting knowledge transfer, capacity building, and socio-economic development within communities. The study highlights the importance of community integration as a strategic imperative for SMEs, emphasizing the need for further research to explore the mechanisms and outcomes of community integration in different contexts.